Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To design an input-output machine, we need to establish the relationship between the input values ([tex]\( x \)[/tex]) and the output values ([tex]\( y \)[/tex]). Based on the given data for [tex]\( x \)[/tex] and [tex]\( y \)[/tex], we can derive the rule.
The table provided is:
[tex]\[ \begin{array}{|c|c|c|c|c|c|c|c|} \hline x & 1 & 3 & 5 & 7 & 9 & 11 & 13 \\ \hline y & 4 & 10 & 16 & 22 & 28 & 34 & 40 \\ \hline \end{array} \][/tex]
1. Analyze the relationship between [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
Let's look at the pairs of [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
- When [tex]\( x = 1 \)[/tex], [tex]\( y = 4 \)[/tex]
- When [tex]\( x = 3 \)[/tex], [tex]\( y = 10 \)[/tex]
- When [tex]\( x = 5 \)[/tex], [tex]\( y = 16 \)[/tex]
- When [tex]\( x = 7 \)[/tex], [tex]\( y = 22 \)[/tex]
- When [tex]\( x = 9 \)[/tex], [tex]\( y = 28 \)[/tex]
- When [tex]\( x = 11 \)[/tex], [tex]\( y = 34 \)[/tex]
- When [tex]\( x = 13 \)[/tex], [tex]\( y = 40 \)[/tex]
2. Find a pattern:
To identify the rule, we observe how [tex]\( y \)[/tex] changes with respect to [tex]\( x \)[/tex]. Let's identify the differences:
- [tex]\( y \)[/tex] when [tex]\( x = 1 \)[/tex] is 4.
- [tex]\( y \)[/tex] when [tex]\( x = 3 \)[/tex] is 10.
- [tex]\( y \)[/tex] when [tex]\( x = 5 \)[/tex] is 16.
- [tex]\( y \)[/tex] when [tex]\( x = 7 \)[/tex] is 22.
- [tex]\( y \)[/tex] when [tex]\( x = 9 \)[/tex] is 28.
- [tex]\( y \)[/tex] when [tex]\( x = 11 \)[/tex] is 34.
- [tex]\( y \)[/tex] when [tex]\( x = 13 \)[/tex] is 40.
Notice the differences in [tex]\( y \)[/tex] when [tex]\( x \)[/tex] is increased by 2 each time:
- [tex]\( y (x = 3) - y (x = 1) = 10 - 4 = 6 \)[/tex]
- [tex]\( y (x = 5) - y (x = 3) = 16 - 10 = 6 \)[/tex]
- [tex]\( y (x = 7) - y (x = 5) = 22 - 16 = 6 \)[/tex]
- [tex]\( y (x = 9) - y (x = 7) = 28 - 22 = 6 \)[/tex]
- [tex]\( y (x = 11) - y (x = 9) = 34 - 28 = 6 \)[/tex]
- [tex]\( y (x = 13) - y (x = 11) = 40 - 34 = 6 \)[/tex]
The output [tex]\( y \)[/tex] increases by 6 for each increase of 2 in [tex]\( x \)[/tex]. This suggests a linear relationship of the form [tex]\( y = ax + b \)[/tex].
3. Formulate the equation:
From the pattern observed, we deduce that for every increase by 1 in [tex]\( x \)[/tex], the [tex]\( y \)[/tex]-value increases by half of 6, which is 3.
Let's check if [tex]\( y = 3x + c \)[/tex] fits:
- When [tex]\( x = 1 \)[/tex]:
[tex]\( 4 = 3(1) + c \)[/tex] --> [tex]\( c = 4 - 3 = 1 \)[/tex]
Hence, the equation can be written as:
[tex]\( y = 3x + 1 \)[/tex]
4. Verify the rule:
Let's verify this rule using the given pairs:
- When [tex]\( x = 1 \)[/tex]: [tex]\( y = 3(1) + 1 = 4 \)[/tex]
- When [tex]\( x = 3 \)[/tex]: [tex]\( y = 3(3) + 1 = 10 \)[/tex]
- When [tex]\( x = 5 \)[/tex]: [tex]\( y = 3(5) + 1 = 16 \)[/tex]
- When [tex]\( x = 7 \)[/tex]: [tex]\( y = 3(7) + 1 = 22 \)[/tex]
- When [tex]\( x = 9 \)[/tex]: [tex]\( y = 3(9) + 1 = 28 \)[/tex]
- When [tex]\( x = 11 \)[/tex]: [tex]\( y = 3(11) + 1 = 34 \)[/tex]
- When [tex]\( x = 13 \)[/tex]: [tex]\( y = 3(13) + 1 = 40 \)[/tex]
All values fit the equation perfectly.
Therefore, the rule for the input-output machine is: [tex]\( y = 3x + 1 \)[/tex].
The table provided is:
[tex]\[ \begin{array}{|c|c|c|c|c|c|c|c|} \hline x & 1 & 3 & 5 & 7 & 9 & 11 & 13 \\ \hline y & 4 & 10 & 16 & 22 & 28 & 34 & 40 \\ \hline \end{array} \][/tex]
1. Analyze the relationship between [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
Let's look at the pairs of [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
- When [tex]\( x = 1 \)[/tex], [tex]\( y = 4 \)[/tex]
- When [tex]\( x = 3 \)[/tex], [tex]\( y = 10 \)[/tex]
- When [tex]\( x = 5 \)[/tex], [tex]\( y = 16 \)[/tex]
- When [tex]\( x = 7 \)[/tex], [tex]\( y = 22 \)[/tex]
- When [tex]\( x = 9 \)[/tex], [tex]\( y = 28 \)[/tex]
- When [tex]\( x = 11 \)[/tex], [tex]\( y = 34 \)[/tex]
- When [tex]\( x = 13 \)[/tex], [tex]\( y = 40 \)[/tex]
2. Find a pattern:
To identify the rule, we observe how [tex]\( y \)[/tex] changes with respect to [tex]\( x \)[/tex]. Let's identify the differences:
- [tex]\( y \)[/tex] when [tex]\( x = 1 \)[/tex] is 4.
- [tex]\( y \)[/tex] when [tex]\( x = 3 \)[/tex] is 10.
- [tex]\( y \)[/tex] when [tex]\( x = 5 \)[/tex] is 16.
- [tex]\( y \)[/tex] when [tex]\( x = 7 \)[/tex] is 22.
- [tex]\( y \)[/tex] when [tex]\( x = 9 \)[/tex] is 28.
- [tex]\( y \)[/tex] when [tex]\( x = 11 \)[/tex] is 34.
- [tex]\( y \)[/tex] when [tex]\( x = 13 \)[/tex] is 40.
Notice the differences in [tex]\( y \)[/tex] when [tex]\( x \)[/tex] is increased by 2 each time:
- [tex]\( y (x = 3) - y (x = 1) = 10 - 4 = 6 \)[/tex]
- [tex]\( y (x = 5) - y (x = 3) = 16 - 10 = 6 \)[/tex]
- [tex]\( y (x = 7) - y (x = 5) = 22 - 16 = 6 \)[/tex]
- [tex]\( y (x = 9) - y (x = 7) = 28 - 22 = 6 \)[/tex]
- [tex]\( y (x = 11) - y (x = 9) = 34 - 28 = 6 \)[/tex]
- [tex]\( y (x = 13) - y (x = 11) = 40 - 34 = 6 \)[/tex]
The output [tex]\( y \)[/tex] increases by 6 for each increase of 2 in [tex]\( x \)[/tex]. This suggests a linear relationship of the form [tex]\( y = ax + b \)[/tex].
3. Formulate the equation:
From the pattern observed, we deduce that for every increase by 1 in [tex]\( x \)[/tex], the [tex]\( y \)[/tex]-value increases by half of 6, which is 3.
Let's check if [tex]\( y = 3x + c \)[/tex] fits:
- When [tex]\( x = 1 \)[/tex]:
[tex]\( 4 = 3(1) + c \)[/tex] --> [tex]\( c = 4 - 3 = 1 \)[/tex]
Hence, the equation can be written as:
[tex]\( y = 3x + 1 \)[/tex]
4. Verify the rule:
Let's verify this rule using the given pairs:
- When [tex]\( x = 1 \)[/tex]: [tex]\( y = 3(1) + 1 = 4 \)[/tex]
- When [tex]\( x = 3 \)[/tex]: [tex]\( y = 3(3) + 1 = 10 \)[/tex]
- When [tex]\( x = 5 \)[/tex]: [tex]\( y = 3(5) + 1 = 16 \)[/tex]
- When [tex]\( x = 7 \)[/tex]: [tex]\( y = 3(7) + 1 = 22 \)[/tex]
- When [tex]\( x = 9 \)[/tex]: [tex]\( y = 3(9) + 1 = 28 \)[/tex]
- When [tex]\( x = 11 \)[/tex]: [tex]\( y = 3(11) + 1 = 34 \)[/tex]
- When [tex]\( x = 13 \)[/tex]: [tex]\( y = 3(13) + 1 = 40 \)[/tex]
All values fit the equation perfectly.
Therefore, the rule for the input-output machine is: [tex]\( y = 3x + 1 \)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.